A Conservationist Menagerie: Redefining The Johannesburg Zoo ThroughA Multi-Species Educational Facility - Jacob, Anneline (University of the Witwatersrand, Johannesburg, 2024)
This architectural project seeks to rectify the injustices that the human-wildlife conflict has had on captive, injured and displaced wildlife and their welfare. Throughout the years human have exerted their dominance over wildlife and the current relationship between humans and animals is described as hierarchical and demonstrates a power dynamic whereby humans view themselves as superior to wildlife. This dynamic and the absence of animals which used to be a part of daily life has resulted in a lack of tangible experiences between species resulting in a knowledge gap and poor understanding of animal welfare. This research project will explore the relationship between humans and wildlife in the context of the Johannesburg Zoo which has faced increasing disapproval from the public as its current design fails to provide adequate landscape habitats and ecological aware facilities for animals, thereby decreasing the educational value and overall experience for the animals and visitors, threatening the welfare of the animals. The zoo represents the ideal testing environment due to its possession of animals in stimulated environments. As one of the largest sites that house wildlife within an urban landscape, it facilitates daily human interactions and is the ideal space to observe co-habitation and multi-species relationships. This will facilitate the development of an alternative zoo model which aims to draw lessons from the precedent "Multispecies Design" by Daniel Metcalfe to influence a shift in the power dynamic by creating interactions that will promote respect between humans, wildlife and nature. This will facilitate reconciliation enabling learning so that humans and animals develop a kinship that fosters coexistence and coadaptation to eliminate conflict and captivity, building wildlife welfare and maintaining resources for future use. The research will be directed through an explorative approach that will include a series of photographs, mapping, and research tabulations to gain an understanding of wildlife habitats and how they may be adapted and recreated in the urban landscape. The research will make use of film and comic-like graphics to illustrate the design and spaces representative of a utopian world, which may be created but has not been accomplished yet.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment, Wits of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Multispecies Design; Human-Animal Coexistence; Captivity & Freedom; Alternative Education Spaces; SDG-4: Quality education